2018
DOI: 10.1536/ihj.17-474
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Association of Serum Uric Acid Levels with Premature Ventricular Contraction

Abstract: In this study, we aim to investigate the association of serum uric acid (SUA) with the prevalence of premature ventricular contraction (PVC). The relationship between SUA and the prevalence of PVC in 98,965 subjects (79,034 male subjects, mean age: 51.9 ± 12.6 years old) in the Kailuan cohort study (n = 101,510, age range: 18-98 years) from June 2006 to October 2007 was investigated. These subjects were divided into five groups on the basis of their SUA levels. A multivariate logistic regression model was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…One study found a correlation between serum UA and PVCs in patients without myocardial infarction or stroke [19]. A gender-specific analysis found a significant correlation between elevated serum UA concentrations and PVC prevalence in men but not in women [4]. This is consistent with the report by Nakanishi et al that showed a positive correlation of serum UA with cardiovascular morbidity and mortality in a large male population, but not in women [20].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…One study found a correlation between serum UA and PVCs in patients without myocardial infarction or stroke [19]. A gender-specific analysis found a significant correlation between elevated serum UA concentrations and PVC prevalence in men but not in women [4]. This is consistent with the report by Nakanishi et al that showed a positive correlation of serum UA with cardiovascular morbidity and mortality in a large male population, but not in women [20].…”
Section: Discussionsupporting
confidence: 77%
“…Thus, it is likely that a sexspecific mechanism may underlie the association between serum UA and cardiovascular disease. The difference between the findings from various studies can be related to ethnic and territorial specificity [4]. In addition, it is likely that the incidence of PVC may be associated with adverse ventricular remodeling associated with UA.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation